1994
DOI: 10.1080/01652176.1994.9694449
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of isospora suis and strongyloides ransomi in suckling piglets in the Netherlands

Abstract: SUMMARYFaecal samples from suckling piglets from 113 litters on 25 farms in the Netherlands were examined to study the prevalence of gastrointestinal parasites, in particular Strongyloides ransomi and Isospora suis. S. ransomi was not found but I. suis was demonstrated in 17 of the 25 farms and in 41 out of 77 litters of these farms (53%). No other parasites were found. On the basis of these results, a longitudinal study on the incidence and significance of I. suis was performed on 10 farms (5 litters/farm). s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 7 publications
2
18
1
Order By: Relevance
“…In Australia Driesen et al (1993) reported I. suis in 53.8% of samples, in Germany I. suis was found to occur in 26.9% of samples (Wieler et al, 2001) and in 42.5% of samples (Niestrah et al, 2002). Eysker et al (1994) in the Netherlands detected I. suis in 36.3% of samples, in repeated samplings isosporosis prevalence among piglets amounted to 53.8%-62.2%. In Northern Europe Roepstorff et al (1998) reported the value 17.2% as average prevalence of isosporosis.…”
Section: Resultsmentioning
confidence: 99%
“…In Australia Driesen et al (1993) reported I. suis in 53.8% of samples, in Germany I. suis was found to occur in 26.9% of samples (Wieler et al, 2001) and in 42.5% of samples (Niestrah et al, 2002). Eysker et al (1994) in the Netherlands detected I. suis in 36.3% of samples, in repeated samplings isosporosis prevalence among piglets amounted to 53.8%-62.2%. In Northern Europe Roepstorff et al (1998) reported the value 17.2% as average prevalence of isosporosis.…”
Section: Resultsmentioning
confidence: 99%
“…Once I . suis has been established in a farm, the infection is probably maintained through transmission from one generation of piglets to the next [7] via contaminated farrowing pens [8,9]. Sows are rarely found to excrete oocysts [9], and may not play a critical role for I .…”
Section: Introductionmentioning
confidence: 99%
“…We were interested to see in our study whether species from wild boars have been transferred to outdoor-kept pigs, particularly on farms close to wild boar habitats. For a speci¢c parasite such as Isospora suis, a study on 25 farms has been published (Eysker et al, 1994). According to the ¢gures of the insurance company for slaughtered animals, more than 10% of the livers were condemned over the last 8 years, indicating a high prevalence of Ascaris suum, despite the availability of very e¡ective anthelminthics (CBS, 2002).…”
Section: Introductionmentioning
confidence: 99%